Analysis of Students’ Science Process Skills Through Inquiry-Based Learning (IBL) in Elementary School - Nazroatul Ummah; Fitria Wulandari (UNDIKMA, 2026)
Science Process Skills (SPS) are fundamental competencies that form the foundation of scientific thinking; however, national achievement levels remain relatively low. This study aims to conduct an in-depth analysis of the achievement profiles of third-grade elementary school students’ SPS indicators through the application of the Inquiry Based Learning (IBL) model to the topic of the five senses. The study employs a descriptive qualitative approach using a single-case study design. The research subjects involved 22 third-grade students at SD Muhammadiyah 1 & 2 Taman, selected through purposive sampling. Data collection was conducted through SPS tests, documentation of student worksheets, and structured interviews, which were then analyzed using the Miles and Huberman model and tested for validity through triangulation of techniques and sources. The results of the study indicate that the implementation of IBL is highly effective in facilitating the mastery of basic science process skills, particularly in the areas of observation and hypothesis formulation. However, achievements in integrated process skills, such as planning experiments, communicating results, and asking questions, are still considered moderate. This suggests that lower-grade students’ mastery of science process skills remains at the guided inquiry level, where students are not yet able to conduct independent inquiry and are still heavily reliant on teacher guidance. The novelty of this study lies in the mapping of the hierarchy of mastery of basic science process skills in lower grades, which demonstrates that content rooted in concrete experiences (the five senses) can accelerate the ability to formulate hypotheses a skill that is theoretically often considered too complex for young children. Practically, this study implies the need for elementary school teachers to design more structured IBL scenarios by providing scaffolding and intensive stimuli to bridge students’ transition toward more open inquiry.